2011
DOI: 10.1016/j.nuclphysa.2011.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic chiral mean field model for finite nuclei

Abstract: Pion is important in Nuclear Physics. Yukawa introduced pion as a mediator of nucleon-nucleon interaction in 1934 [1]. However, Nuclear Physics started by shell model with strong spin-orbit interaction in 1949 by Meyer and Jensen. The shell model is a phenomenological model and it has to be explained from more basic dynamics by explicitly using pion. The pion had not played the central role in nuclear physics until recent years. In this paper, we would like to discuss the recent development on the role of pion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The correlation term between the 2p-2h states with the Hartree-Fock space (0p-0h states) is very similar to that of the G-matrix theory in an infinite system [17]. A prototype study of the present formalism was performed within the Hartree approximation including 2p-2h states for light nuclei 4 He, 12 C and 16 O [18,19].…”
Section: Introductionmentioning
confidence: 87%
“…The correlation term between the 2p-2h states with the Hartree-Fock space (0p-0h states) is very similar to that of the G-matrix theory in an infinite system [17]. A prototype study of the present formalism was performed within the Hartree approximation including 2p-2h states for light nuclei 4 He, 12 C and 16 O [18,19].…”
Section: Introductionmentioning
confidence: 87%
“…In Refs. [32,33], it has been suggested that tensor contribution is suppressed in 16 O, since 2p2h excitation from the lowest s shell to the p shell is forbidden at the shell model limit. This is true; however tensor contribution turned out to be large in 16 O because of the clustering effect of four α's.…”
mentioning
confidence: 99%